Research in the Faculty of Basic Sciences. Results for Social Appropriation (2024)
As the Faculty of Basic Sciences committed to research, innovation, and social appropriation of knowledge, I have the pleasure of presenting you from our 22 research groups the results of research assigned to the Vice-Rector’s Office for Research, Innovation, and Extension of the Technological University of Pereira, which are linked to fundamental disciplines composed of the basic sciences such as biology, chemistry, geology, and mathematics. Since basic sciences constitute a fundamental basis for each research and reinforce the influence they have had throughout history on the development of science and technology.